Interactive governance: advancing the paradigm / by Jacob Torfing...[et al] - Jacob Torfing...[et al] (Oxford, 2012)
This book helps to clarify this conceptual muddle by concentrating on one variety of governance-interactive governance.
Keywords: Governance